Incidence of personal and contextual factors on the use of technological resources by students in Latin America - Cebrián-Cifuentes, Sara; Almerich, Gonzalo; Suárez-Rodríguez, Jesús; Pedró, Francesc (Education Policy Analysis Archives, 2021)
The use of information and communication technologies (ICT) by students reflects the appropriateness of the ICT integration process. However, the typology of ICT use by students has not been established empirically based on their use at home and at the school. Thus, the purpose of the article is to determine the structure of ICT use by students, together with the influence of personal and contextual factors. A correlational design has been used, with the sample being the sixth-grade students in Latin America who answered the questionnaire on ICT use in the Third Regional Comparative and Explanatory Study (TERCE). The data analysis performed is descriptive statistics, Multivariate Analysis of Variance (MANOVA) and Categorical Principal Components analysis (CATPCA). The results obtained through the descriptive statistics show how the students make a greater use of technological resources in the area of free time than in the academic area. It has been found, by means of a categorical principal components analysis (CATPCA), that student use is structured in three planes: personal, non-school academic and school academic. In addition, the results obtained from the MANOVA indicate that the personal and contextual factors influence the use of ICT, essentially the availability of technological devices and the Internet connection. In the light of the results, it is recommended to implement programs that favour non-school academic use of ICT by students.